Spatial resolution improvement for an optical transition radiation monitor by asymmetric light collection; Optics Express; Vol. 26, iss. 23 - Potylitsyn A. P. Alexander Petrovich; Sukhikh L. G. Leonid Grigorievich; Kube G. Gero; Novokshonov A. I. Artem Igorevich (2018, 2018)
Title screen